Modeling electrolysis in reduced gravity: producing oxygen from in-situ resources at the moon and beyond - Burke, Paul A.; Nord, Michael E.; Hibbitts, Charles A.; Berdis, Jodi R. (Frontiers in Space Technologies, 2024)
Molten Regolith Electrolysis, as an in-situ resource utilization (ISRU) technology, has the potential to enable the production of oxygen and metallic alloys on the Lunar surface; opening new doors in Cis-Lunar, and eventually Martian space exploration. This research studies the fundamental physics which govern the formation, growth, detachment, and rise of electrolytic bubbles. To this end, computational fluid dynamic (CFD) models were developed and run, to simulate water electrolysis, molten salt electrolysis (MSE), and molten Lunar regolith (MRE) electrolysis across multiple reduced gravity levels. The results demonstrate that reduced gravity, electrode surface roughness (possibly due to surface degradation), fluid properties, and electrode orientation can all affect electrolytic efficiency and possibly even stall electrolysis by delaying bubble detachment. The findings of this research must be considered when designing and operating electrolysis systems at reduced gravity levels.